PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING UNTUK PEMBELAJARAN MENULIS TEKS DESKRIPSI - Pendri, Apri; Atmazaki, Atmazaki; Asri, Yasnur (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT The purpose of this study was to explain the validity, practicality, and effectiveness of problem based learning student worksheet for learning to write description text. This type of research was the development of research with the Research and Development (R&D) methode. Products that was produced in this research was the problem based learning student worksheet for learning to write a valid, practical, and effective description text . The validity of the student worksheet was 96,87% with a valid category. The value practicalities of the student worksheet from teachers was 89,84% that was  categorized as very practical. The practicalities value of the student worksheet of the students was 89,63% categorized as very practical. The resulting student worksheet was declared effective because the average value of the writing skills of students by 83,21 description text. Kata Kunci:  pengembangan, Lembar Kerja Peserta Didik, Problem Based Learning, teks deskripsi